Mossbauer and mineral magnetic studies on archaeological potteries from Adhichanallur, Tamilnadu, India - Venkatachalapathy, R.; Bakas, T.; Basavaiah, N.; Deenadayalan, K. (My University, 2008)
Megalithic potteries collected from Adhichanallur, Tamilnadu, India (Lat. 844 N; Long. 7742 E) have been subjected to various spectroscopic and rock magnetic studies. The type of clay, their origin, level of structural deformation due to firing, firing temperature and atmospheric condition followed during making the potteries are analyzed. The potteries were subjected to Mossbauer and X-ray diffraction studies to analyze the iron phases in them. It is found that the samples were made of local clay (red clay), fired above 600°C under open atmospheric and/or reduced atmospheric conditions and air has been allowed during cooling. The Mossbauer spectra reveal the presence of Fe3+, Fe2+ and iron oxides of hematite and magnetite. The firing temperature and firing conditions established from Mossbauer studies are similar to the observation made from FT-IR studies. The magnetic mineral types, the mass fractions and the domain states of the constituent magnetic grains were elucidated from a range of rock magnetic measurements including variation of susceptibility with low field, frequency and temperature, hysteresis parameters and isothermal remanence acquisition data. The magnetic mineralogy of most pottery samples was dominated by magnetite/(titano) magnetite, while magnetic grain size spectrum varies from very fine (super paramagnetic) to fine (stable single domain, pseudo single domain). The reversible thermo magnetic behavior reflects no mineralogical transformations during reheating and all the samples show same Curie temperature 580°C due to magnetite. From the above information it is demonstrated that these samples are suitable for determining the reliable ancient geomagnetic field intensity values existed during that period.
Keywords: Archaeological pottery; Maussbauer spectroscopy; Rock-magnetism; Tamilnadu